Interference of soil use and occupation in water quality in a watershed with critical water availability - Guimarães, Túlio Machado Humberto; Salla, Marcio Ricardo; Pereira, Carlos Eugênio; Justo, Bruno Braga [UNESP]; Riquieri, Juliana Corrêa (My University, 2019)
The maximum surface flow in Ribeirão do Salitre, Triângulo Mineiro, exceeds the maximum allowed by the current legislation and allocates, at the head of the main tributary, the pit of a phosphate mine. The calibration of the mathematical model of self-purification using the QUALI-TOOL tool was carried out in the dry and rainy period. The influence of soil use and occupation on water quality in different scenarios was evaluated using the MQUAL model to estimate the pollutant loads. The scenarios evaluated the progress of mining, agriculture and livestock activities on the natural soil. Based on the CONAMA Resolution 357: 2005, for class 2 river, the nitrate concentration was below the maximum allowed in all scenarios, that is, 10 mg / L. The ammoniacal nitrogen presented a high concentration only in the scenario in which it was considered 80% of the total area occupied by agriculture, with values higher than 3.7 mg / L. In all scenarios, the parameters BOD, total phosphorus and Escherichia Coli remained above the maximum allowed by the resolution, which are 5.0 mg / L, 0.05 mg / L, 1000 NMP / 100 mL, respectively. The study portrays the importance of planning and of management of water resources in the preservation of surface water quality.
Interferência do uso e ocupação do solo na qualidade da água em bacia hidrográfica com disponibilidade hídrica crítica
Keywords: Land use and occupation; MQUAL; QUALI-TOOL; Ribeirão do Salitre; Water quality